2022
DOI: 10.1021/acs.bioconjchem.2c00465
|View full text |Cite
|
Sign up to set email alerts
|

H3TPAN-Triazole-Bn-NH2: Tripicolinate Clicked-Bifunctional Chelate for [225Ac]/[111In] Theranostics

Abstract: A new, high-denticity, bifunctional ligandH3TPAN-triazole-Bn-NH2has been synthesized and studied in complexation with [225Ac]Ac3+ and [111In]In3+ for radiopharmaceutical applications. The bifunctional chelator is readily synthesized, using a high-yielding four-step prep, which is highly adaptable and allows for straightforward incorporation of different covalent linkers using CuI-catalyzed alkyne–azide cycloaddition (click) chemistry. Nuclear magnetic resonance (NMR) studies of H3TPAN-triazole-Bn-NH2 with La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Because we had previously observed excellent stability of both complexes of unfunctionalized py-macrodipa in human serum, this result demonstrates how radiometal complex stability can be substantially different when incorporated into targeted agents, consistent with similar observations in the literature. [36,37] In any case, this study provides another recent example of leveraging the same construct for targeted nuclear medicine applications with two chemically disparate radiometals, [10][11][12] like 132/135 La 3 + and 47 Sc 3 + in this case. We further note that these initial in vivo studies are limited by the lack of additional time points and the lower molar activity of the 47 Sc used.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Because we had previously observed excellent stability of both complexes of unfunctionalized py-macrodipa in human serum, this result demonstrates how radiometal complex stability can be substantially different when incorporated into targeted agents, consistent with similar observations in the literature. [36,37] In any case, this study provides another recent example of leveraging the same construct for targeted nuclear medicine applications with two chemically disparate radiometals, [10][11][12] like 132/135 La 3 + and 47 Sc 3 + in this case. We further note that these initial in vivo studies are limited by the lack of additional time points and the lower molar activity of the 47 Sc used.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have revealed that a bispidine ligand can rapidly and stably bind to both 225 Ac 3+ and 177 Lu 3+ [10] . Likewise, some acyclic picolinate ligands were also found to mutually stabilize 225 Ac 3+ and 111 In 3+ [11,12] . In our contribution to this area, we recently reported a unique class of chelators that possess dual size selectivity, a property that confers good affinity for both the large and small metal ions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Structure of H 3 TPAN-triazole-Bn-NH 2 (A) as well as DFT-calculated structures of H 3 TPAN-triazole-Bn-NH 2 bound to (B) Ac 3+ and (C) In 3+ . Panels (B,C) were reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…108 Finally, this approach has recently been extended beyond the realm of 99m Tc and its congeners by Wharton et al In this case, the investigators used the CuAAC reaction to create a bifunctional chelator, H 3 TPAN-triazole-Bn-NH 2 , in which the 1,2,3-triazole both coordinates the radiometal and attaches the chelator to the vector in question (Figure 9). 109 This acyclic chelator offers several advantages over extant options, including its synthetic accessibility, lack of steric hindrance, and compatibility with both 225 Ac and 111 In.…”
Section: ■ Introductionmentioning
confidence: 99%